CHALLENGES OF THE INDONESIAN REPUBLIC GENERAL ELECTION COMMISSION (KPU RI) TO INCREASE VOTER PARTICIPATION - Andina Elok Puri Maharani; Rizma Dwi Nidia (UNTAG Law Review, 2019)
This research examines problems that arise and become obstacles in the process of organizing general elections and the challenges of the General Election Commission (KPU) in increasing voter participation in general elections.The purpose of this study is to find out what obstacles arise in the implementation of the General Election related to the role of the KPU to increase public participation in general elections. This type of research is empirical research and the data used are primary data by conducting interviews with KPU commissioners accompanied by an analysis of secondary data in the form of legislation. The results of this study indicate that barriers that can interfere with the process of holding elections, arise from news hoaxes and some obstacles that are classified based on the group of voters. Every segment of society has different needs, so the method used to increase community participation is tailored to the needs of the community in each segment.